2005
DOI: 10.1001/archneur.62.10.1531
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With β-Amyloid(1-42) Immunotherapy in Preimmunization Gene Expression Patterns of Blood Cells

Abstract: Background: A phase 2a, double-blind, placebocontrolled, multicenter study was conducted to evaluate safety, tolerability, and pilot efficacy of immunization with ␤-amyloid (1-42) in patients with Alzheimer disease. Six immunizations were planned but were halted when meningoencephalitis was recognized as an adverse event in 6% of immunized patients. Objective: To identify biomarkers associated with both the risk of meningoencephalitis and antibody responsiveness. Participants: One hundred fifty-three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The versatility of the T1 Th-cell epitope with different mouse MHC class II loci and different species make these immunogens an attractive candidate for additional studies in particular with other mouse strains or species. A recent publication analyzing gene expression profiles of patients from an AN-1792 immunization trial suggest reduced abilities to mount an effective immune response against A␤, mainly because of the advanced age of the patients (O'Toole et al, 2005). Therefore, activation of the immune system in AD patients to mount an effective antibody response against A␤ and, in particular, to induce immunological memory, may require a strong universal T-cell epitope such as T1 that does not cross-react with A␤ T-cell epitope(s).…”
Section: Discussionmentioning
confidence: 99%
“…The versatility of the T1 Th-cell epitope with different mouse MHC class II loci and different species make these immunogens an attractive candidate for additional studies in particular with other mouse strains or species. A recent publication analyzing gene expression profiles of patients from an AN-1792 immunization trial suggest reduced abilities to mount an effective immune response against A␤, mainly because of the advanced age of the patients (O'Toole et al, 2005). Therefore, activation of the immune system in AD patients to mount an effective antibody response against A␤ and, in particular, to induce immunological memory, may require a strong universal T-cell epitope such as T1 that does not cross-react with A␤ T-cell epitope(s).…”
Section: Discussionmentioning
confidence: 99%
“…However, the trial had to be prematurely stopped because of the development of severe meningoencephalitis in some patients related to vaccine-generated cytotoxic T cells. Recent analysis has demonstrated that prevaccine gene expression patterns indicative of proinflammatory pathways were associated with development of immunotherapy-related meningoencephalitis, whereas ex- pression of genes related to protein synthesis, protein trafficking, and DNA repair were strongly associated with a beneficial immunoglobulin G response to immunization (O'Toole et al, 2005).…”
Section: Neuroinflammation/neurodegenerationmentioning
confidence: 99%
“…Recently, candidate biomarkers of risk for the development of meningoencephalitis have been identified in the patients enrolled in the phase IIa AN1792 trial [61]. In future trials, these potential markers as well as the haplotype of the individuals should be considered prior to enrollment.…”
Section: An1792 -Encephalitis Amyloid Clearance and Cognitive Assessmentioning
confidence: 99%